STUDENT-CENTERED LEARNING IN RELATION TO CLASS PERFORMANCES AND SOFT SKILLS: A META-ANALYSIS AND SYSTEMATIC REVIEW - Elisabeth Rukmini; Cindy Cindy; Pricillia Tanoto (Jurnal Pendidikan Kedokteran Indonesia: The Indonesian Journal of Medical Education, 2018)
Background: Studies showed that SCL improved quality of medical education through knowledge acquisition, class performance, students’ attitude and soft skills. Although research about SCL and its impact has been widely known, overall correlation of SCL to the class performances has not yet been established. Strong correlation between SCL to class performances would serve the purpose of teaching and learning and more importantly would answer the skepticism of institution or faculty members in implementing SCL. In addition, learning through systematic review of others’ studies, how SCL influenced soft skill aspects would be benefited for medical educators. Soft skills such as learning motivation, communication skills, and teamwork may lead educators to the favor of SCL approaches. This review was to find the correlation of student-centered learning to the students’ performances and soft skill aspects in medical education.Method: To find the correlation of the SCL and class performances, we used meta-analysis. We also performed a systematic review to qualitatively find the relationship between SCL and other aspects, such as teamwork, communication skills, and learning motivation. Literatures were filtered from databases of: Proquest, Springerlink, Biomed Central (BMC) open, BMJ open, and Google Scholar. The inclusion criteria were published empirical articles (2000-2013) reported SCL’s effect on class performances or other aspects (learning motivation, teamwork, communication skills). We utilized PRISMA protocol to filter the inclusion articles. By reading abstracts and further snowballing searching, we found 12 articles for the meta-analysis and 33 articles for the systematic review.                                                                 Results: Among 12 articles of the meta-analysis, 9 articles showed positive correlation between SCL and class performances. Three studies reported that SCL had no effect on the class performances. None of the articles reported any negative impact. We utilized the Comprehensive Meta-Analysis software to analyze the data and found r = 0.46 and 95% CI: 0.32 - 0.57. It showed a statistically significant correlation between SCL and class performances. On the systematic review, we found that SCL improved communication skills, team work, and learning motivation.Conclusion: From the meta-analysis we found that SCL improved class performances about 46%. It was showed that SCL methods were superior in improving soft skills such as communication skills, teamwork, and learning motivation.